The dark side of perceived corruption: Mediating mechanism between love of money and evil behavior - Ikhsan Maksum; Mega Noerman Ningtyas (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
Many studies about unethical behavior (evil behavior) in the workplace have underlying various research related to love of money and perception of corruption as in this research. One of the main ideas that emerged is “The love of money is a root of all kinds of evil” Timothy, 6:10. In most studies, there is a gap and lack of prior research involving the mechanism of indirect effect between the love of money behavior and unethical behavior in public sector institutions. In this research, we focus on the role of mediation between the perception of corruption and love of money toward unethical behavior. The researcher spread the questionnaire for obtained 149 respondents who are an employee from the public sector institution. Meanwhile, the research method that we use is a quantitative study, which allows for doing the study with a fast time and broad generalizability. We find that perception of corruption could partially mediate the effect between the love of money and unethical behavior in public sector employees. This study proves that employees who work in public sector institutions have a corruption perception that can trigger evil behavior. employees who have a strong orientation towards money are more likely to try to earn more money to enrich themselves, and then employees engage in unethical behavior.